(untitled) (The Review of Diabetic Studies, 2025)
Introduction: Stroke is a leading cause of mortality and disability worldwide, and acute stroke care is highly dependent upon the rapid recognition and intervention of frontline emergency providers. Given the high prevalence of stroke in Saudi Arabia, and the fact that Emergency Medical Technician-Paramedics (EMT-Paramedics) may be the first emergency personnel to encounter a patient with acute stroke, we sought to understand their knowledge, experience, and training needs in recognition and management of stroke, and identify gaps and opportunities for targeted educational interventions. Method: An observational cross-sectional electronic survey of EMT-Paramedics from selected emergency medical services in Saudi Arabia was performed between August 2023 and October 2024 using a validated questionnaire to assess their knowledge of stroke symptoms, risk factors, and acute management, and their training background and clinical exposure. Results: A total of 142 EMT-Paramedics from King Fahd Medical City in Riyadh participated in the survey (83.6% response rate). Common stroke symptoms (e.g., facial droop [92%], unilateral weakness [91%], and speech disturbance [88%]) were recognized by most participants, while fewer recognized less obvious signs (e.g., visual disturbance [46%], headache [38%], and ataxia [35%]). Knowledge of risk factors was moderate (e.g., atrial fibrillation [58%] and hypertension [69%]), and years of experience and prior stroke training were significantly associated with higher knowledge scores (r = 0.28, p < .001; r = 0.27, p = .003), with EMT-Paramedics with more than five years of experience (77.9% vs. 71.0%, p = .005) or previous stroke training (79.2% vs. 70.4%, p < .001) reporting greater confidence and accuracy in stroke recognition and acute management. Conclusions: The results emphasize significant training gaps in acute stroke care among EMT-Paramedics in Saudi Arabia, and regular structured training programs and continuous professional development are suggested to enhance early recognition and management skills, particularly for less experienced providers, to improve patient outcomes and optimize the prehospital stroke care system.